2018
DOI: 10.5194/hess-22-6357-2018
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the effect of rainfall on the surface temperature of a tropical lake

Abstract: Abstract. We make use of a unique high-quality, long-term observational dataset on a tropical lake to assess the effect of rainfall on lake surface temperature. The lake in question is Lake Kivu, one of the African Great Lakes, and was selected for its remarkably uniform climate and availability of multi-year over-lake meteorological observations. Rain may have a cooling effect on the lake surface by lowering the near-surface air temperature, by the direct rain heat flux into the lake, by mixing the lake surfa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 66 publications
2
22
0
Order By: Relevance
“…Compared to other meteorological variables known to influence the surface temperature of lakes (Edinger, Duttweiler, & Geyer, 1968), the influence of precipitation on the lake surface temperature is relatively unexplored. One exception is the study of Rooney, van Lipzig, and Thiery (2018), who demonstrated that in tropical Lake Kivu, the surface temperatures cooled by ~0.3°C as a result of precipitation. The change was explained, in part, by the influence of precipitation on (a) the surface heat budget via the rain heat flux (where the rain is cooler than the lake surface temperature); and (b) its influence on surface mixing both directly through enhanced kinetic energy and indirectly by modifying convective mixing in the surface layer (Rooney et al, 2018).…”
Section: Lake and Watershed Attributes As Mediators Of Storm Impactsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other meteorological variables known to influence the surface temperature of lakes (Edinger, Duttweiler, & Geyer, 1968), the influence of precipitation on the lake surface temperature is relatively unexplored. One exception is the study of Rooney, van Lipzig, and Thiery (2018), who demonstrated that in tropical Lake Kivu, the surface temperatures cooled by ~0.3°C as a result of precipitation. The change was explained, in part, by the influence of precipitation on (a) the surface heat budget via the rain heat flux (where the rain is cooler than the lake surface temperature); and (b) its influence on surface mixing both directly through enhanced kinetic energy and indirectly by modifying convective mixing in the surface layer (Rooney et al, 2018).…”
Section: Lake and Watershed Attributes As Mediators Of Storm Impactsmentioning
confidence: 99%
“…One exception is the study of Rooney, van Lipzig, and Thiery (2018), who demonstrated that in tropical Lake Kivu, the surface temperatures cooled by ~0.3°C as a result of precipitation. The change was explained, in part, by the influence of precipitation on (a) the surface heat budget via the rain heat flux (where the rain is cooler than the lake surface temperature); and (b) its influence on surface mixing both directly through enhanced kinetic energy and indirectly by modifying convective mixing in the surface layer (Rooney et al, 2018). Turbidity also plays a role in water temperature, as suspended solids in water absorb and scatter sunlight, with turbid near‐surface water layers warmer than clear near‐surface water layers (Paaijmans, Takken, Githeko, & Jacobs, 2008).…”
Section: Lake and Watershed Attributes As Mediators Of Storm Impactsmentioning
confidence: 99%
“…Within our observed range of storminduced epilimnetic temperature changes, decreases were larger in shallow and medium-depth lakes compared to deep lakes, but only for windstorms. The effects of rain on epilimnetic temperatures may be less than wind because of the variability in rainwater and runoff temperature, which depend on the season and climate (Thompson et al 2008;Doubek et al 2015;Rooney et al 2018). Conversely, the potential for wind to affect water temperature more directly scales with lake morphometry and the distribution of heat vertically in lakes (Horn et al 1986;Stockwell et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, storms can alter thermal stratification during the thermally stratified period (Jennings et al 2012;de Eyto et al 2016;Kasprzak et al 2017) and deepen the thermocline, sometimes resulting in complete mixing of the water column (Yount 1961;Klug et al 2012;Abell and Hamilton 2015). In stratified lakes, epilimnetic temperatures may decrease because of colder water from the hypolimnion mixing into the epilimnion (Znachor et al 2008;Umaña-Villalobos 2014), upwelling, internal waves breaking at the shore, or heat flux at the lake surface altered by wind, rain, or changes in air temperature (e.g., Andreas et al 1995;Kasprzak et al 2017;Rooney et al 2018). However, the extent of temperature change from storm events also depends on a variety of environmental and lake characteristics (Padisák et al 1988;Kuha et al 2016;Andersen et al 2020), such as the frequency of storm events (Smits et al 2020), internal seiche dynamics (Woolway et al, 2018), lake mixing regime (Jennings et al 2012;Kuha et al 2016), and the ratio of the watershed area to the lake surface area (WA:SA) (Jennings et al 2012;Klug et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Methane (CH 4 ) is the second-most-important greenhouse gas contributing to the anthropogenic radiative forcing of the atmosphere, and its atmospheric content has risen 2.5-fold since the Industrial Age. During the last decades, significant efforts have been made to better estimate methane contributions of natural and anthropogenic sources to the global atmospheric budget (Kirschke et al, 2013;Saunois et al, 2019). The development of more advanced techniques allowed the recognition of a larger number of sources, which, coupled with the improvements in the modeling, led to continuous rectifications of this budget (Hamdan and Wickland, 2016).…”
Section: Introductionmentioning
confidence: 99%